2014
DOI: 10.4238/2014.december.18.10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic identification of a novel 1AL.1RS translocation line with powdery mildew resistance

Abstract: ABSTRACT.A wheat germplasm line 13-2-2 with resistance to powdery mildew was isolated; this line was derived from common wheat cv. W770B and rye, Secale cereale L. (2n = 2x = 14, RR). The line was characterized based on cytological, genomic in situ hybridization (GISH), sequence-characterized amplified region (SCAR), and simple sequence repeat (SSR) analyses. The mitotic and meiotic investigations showed that the chromosome number and configuration of 13-2-2 were 2n = 42 = 21 II. GISH using rye genomic DNA as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Recently, PM disease resistance has been reported in cucumber, wheat, and grapevine (Zhou et al, 2013;Alam et al, 2014;Lu et al, 2014;Zhang et al, 2014). In strawberry (Fragaria x ananassa Duchesne), cleaved amplified polymorphic sequence markers related to PM resistance have been developed (Heejeong et al, 2015), and interactions between strawberry and PM have been revealed using the RNA-seq method (Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PM disease resistance has been reported in cucumber, wheat, and grapevine (Zhou et al, 2013;Alam et al, 2014;Lu et al, 2014;Zhang et al, 2014). In strawberry (Fragaria x ananassa Duchesne), cleaved amplified polymorphic sequence markers related to PM resistance have been developed (Heejeong et al, 2015), and interactions between strawberry and PM have been revealed using the RNA-seq method (Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%